A review of climate change impacts on migration patterns of marine vertebrates in Arctic and Subarctic ecosystems - Kuletz, Katherine J.; Ferguson, Steven H.; Frederiksen, Morten; Gallagher, Colin P.; Hauser, Donna D. W.; Hop, Haakon; Kovacs, Kit M.; Lydersen, Christian; Mosbech, Anders; Seitz, Andrew C. (Frontiers in Environmental Science, 2024)
Climate change is impacting marine ecosystems throughout the circumpolar Arctic, altering seasonal habitats and the food bases for fishes, seabirds, and marine mammals. Arctic and Subarctic regions provide resources for resident species and for species that migrate to the north from more southerly regions. Changes in northerly latitudes thus impact endemic as well as non-endemic animals. Herein, we review what is known about climate-driven changes in the migration patterns of Arctic and Subarctic marine vertebrates, including: (1) Arctic residents with seasonal movements -those fishes, seabirds, and marine mammals that complete their entire life cycle within the Arctic but exhibit seasonal movements;(2) Breeding migrants -many seabirds enter the Arctic to breed and subsequently migrate south in the fall; and (3) Summer visitors for feeding -certain seabirds and marine mammals arrive during the northern summer to feed on abundant prey though they breed elsewhere. Migratory movements are often driven by the timing and extent of sea ice, which defines suitable habitat for some animals and affects access to open water and prey for others. Longer open-water seasons, warmer ocean temperatures, and stronger winds have resulted in earlier, but decreased sea-ice primary production and, conversely, extended open-ocean plankton blooms, resulting in altered prey types and distributions. A common thread among taxa is that shifts in timing and distribution of migrating animals indicate they are traveling farther north, or shifting longitudinally, and migrations are occurring over longer seasonal time frames. Species performing multiple lifetime migrations or long-distance migrants may need to adjust migration timing or routing iteratively to match changes in marine productivity. Altered animal distributions or phenology, and reduced sea ice, affects access to animals that are critical nutritional, economical, and cultural components of the lives of Indigenous people in the Arctic. Ongoing changes challenge the resilience and adaptability of Arctic people and ecosystems, and will require adaptive research and management approaches.